The Impact of High Dose Glucocorticoids on Bone Health and Fracture Risk in Systemic Vasculitides - Box, Christopher David; Cronin, Owen; Hauser, Barbara (Frontiers in Endocrinology, 2022)
Systemic vasculitides are a range of conditions characterised by inflammation of blood vessels which may manifest as single organ or life-threatening multisystem disease. The treatment of systemic vasculitis varies depending on the specific disease but historically has involved initial treatment with high dose glucocorticoids alone or in conjunction with other immunosuppressive agents. Prolonged glucocorticoid treatment is frequently required as maintenance treatment. Patients with small and large vessel vasculitis are at increased risk of fracture. Osteoporosis may occur due to intrinsic factors such as chronic inflammation, impaired renal function and to a large extent due to pharmacological therapy with high dose glucocorticoid or combination treatments. This review will outline the known mechanism of bone loss in vasculitis and will summarize factors attributing to fracture risk in different types of vasculitis. Osteoporosis treatment with specific consideration for patients with vasculitis will be discussed. The use of glucocorticoid sparing immunosuppressive agents in the treatment of systemic vasculitis is a significant area of ongoing research. Adjunctive treatments are used to reduce cumulative doses of glucocorticoids and therefore may significantly decrease the associated fracture risk in patients with vasculitis. Lastly, we will highlight the many unknowns in the relation between systemic vasculitis, its treatment and bone health and will outline key research priorities for this field.